2019
DOI: 10.1038/s41612-019-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

‘Eastern African Paradox’ rainfall decline due to shorter not less intense Long Rains

Abstract: An observed decline in the Eastern African Long Rains from the 1980s to late 2000s appears contrary to the projected increase under future climate change. This "Eastern African climate paradox" confounds use of climate projections for adaptation planning across Eastern Africa. Here we show the decline corresponds to a later onset and earlier cessation of the long rains, with a similar seasonal maximum in area-averaged daily rainfall. Previous studies have explored the role of remote teleconnections, but those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
139
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 69 publications
22
139
1
Order By: Relevance
“…One of the major drivers of cessation over the equatorial region is the Somali jet (Camberlin et al 2010). It is projected that the Somali jet will strengthen in the future, Zhou 2015, Wainwright et al 2019) thus in agreement with Wainwright et al (2019) we postulate that this could be one of the drivers of early cessation over the equatorial region. The dipole observed in figures 2(d) and (h), can be attributed to the trapping of ITCZ over eastern Africa by the Saharan heat low, which is projected to strengthen (Dunning et al 2018).…”
Section: Projected Changes In Onset and Cessation 411 March To Maysupporting
confidence: 75%
See 1 more Smart Citation
“…One of the major drivers of cessation over the equatorial region is the Somali jet (Camberlin et al 2010). It is projected that the Somali jet will strengthen in the future, Zhou 2015, Wainwright et al 2019) thus in agreement with Wainwright et al (2019) we postulate that this could be one of the drivers of early cessation over the equatorial region. The dipole observed in figures 2(d) and (h), can be attributed to the trapping of ITCZ over eastern Africa by the Saharan heat low, which is projected to strengthen (Dunning et al 2018).…”
Section: Projected Changes In Onset and Cessation 411 March To Maysupporting
confidence: 75%
“…These results are consistent with Dunning et al (2018) who found that CMIP5 models over the equatorial region projected early-onset and cessation. Onset over equatorial East Africa is linked to the 700 mb zonal winds, the Madden Julian Oscillation, and sea surface temperature in the western Indian Ocean (Camberlin and Okoola 2003, Pohl and Camberlin 2006, Zaitchik 2017, Wainwright et al 2019. It is projected that in the future the MJO precipitation amplitude will increase (Maloney et al 2019), thus affecting the rainfall onset, in this case leading to earlyonset.…”
Section: Projected Changes In Onset and Cessation 411 March To Maymentioning
confidence: 99%
“…Lyon and Vigaud [15] show that the decline in MAM rains in East Africa started in 1999 and link the timing of the abrupt shift to the Pacific Decadal Variability (PDV). Wainwright et al [54] believe that the drying trend is caused by shortening of the MAM rainy season due to more rapid movement of the ITCZ rather than simply decreasing rainfall amounts. They attribute the faster migration of the ITCZ to an increasing pressure gradient caused by the warming SSTs to the north in the Arabian Sea in JJA, and to the south near Madagascar in DJF.…”
Section: Variabilitymentioning
confidence: 99%
“…Floods can lead to the spreading of water-borne diseases, as well as damage infrastructure and crops (ACAPS, 2018;Kilavi et al, 2018;The Guardian, 2018). But in more recent decades, droughts have been prevalent during the long rains (March-May), and these recent dry decades have been extensively studied (Maidment et al, 2015;Rowell et al, 2015;Hoell et al, 2017;Wainwright et al, 2019). The apparent conflict between the recent dry period and climate projections of increased rain has been referred to as the "Eastern African Climate Paradox" (Rowell et al, 2015;Wainwright et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…But in more recent decades, droughts have been prevalent during the long rains (March-May), and these recent dry decades have been extensively studied (Maidment et al, 2015;Rowell et al, 2015;Hoell et al, 2017;Wainwright et al, 2019). The apparent conflict between the recent dry period and climate projections of increased rain has been referred to as the "Eastern African Climate Paradox" (Rowell et al, 2015;Wainwright et al, 2019). Understanding the processes that control the large variability in East Africa long rains is essential to provide reliable warnings and forecasts to the population, as well as to be able to assess confidence in projections of climate change in the region.…”
Section: Introductionmentioning
confidence: 99%